HYPOTHESIS TESTING IN MEDICAL RESEARCH: A KEY STATISTICAL APPLICATION - Kumar, Ashok (Journal of Universal College of Medical Sciences, 2016)
“Hypothesis testing” is an integral and most important component of research methodology, in all researches, whether in medical sciences, social sciences or any such allied field. It is a guideline in planning, implementation and getting final results thereof, in undertaking any research work. The present paper, in this direction, is designed mainly as a key note, to highlight the basics towards hypothesis, testing its validity i.e. Acceptance “or” rejection and finally interpreting the tenability of selected variables as a solution to the postulated “ research problem ”. To supplement with , a few problem based illustrations (pbi)s have also been incorporated accordingly. Journal of Universal College of Medical Sciences (2015) Vol.03 No.02 Issue 10 Page: 53-56